2018
DOI: 10.1177/0095244318780539
|View full text |Cite
|
Sign up to set email alerts
|

Reclaiming of waste guayule natural rubber vulcanizate—reclaim rubber for green tire applications: An approach for sustainable development

Abstract: This article illustrates the reclaiming of guayule natural rubber (GNR) vulcanizate by bis[3-(triethoxysilyl)propyl] tetrasulfide (TESPT), and as-grown reclaim rubber facilitates the silica dispersion in GNR product application without adding any coupling agent. This article deals with the performance evaluation of silica-filled revulcanizates with promising application in green tire. The extent of reclaiming was monitored through the measurement of sol content, cross-link density, Mooney viscosity, and degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…To have useful properties, devulcanized rubber must be vulcanized again, i.e., be revulcanized. In recent literature, several articles analyzing the revulcanization of devulcanized rubbers are found but many in the form of blends , or composites containing reinforcement agents such as silica. ,, Formela et al analyzed the influence of different vulcanization system types on the revulcanization behavior of thermomechanical devulcanized ground tire rubber (GTR). The results showed that the revulcanization system used, i.e., the type of accelerator, strongly influenced the revulcanization behavior, which consequently resulted in different static and dynamic mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…To have useful properties, devulcanized rubber must be vulcanized again, i.e., be revulcanized. In recent literature, several articles analyzing the revulcanization of devulcanized rubbers are found but many in the form of blends , or composites containing reinforcement agents such as silica. ,, Formela et al analyzed the influence of different vulcanization system types on the revulcanization behavior of thermomechanical devulcanized ground tire rubber (GTR). The results showed that the revulcanization system used, i.e., the type of accelerator, strongly influenced the revulcanization behavior, which consequently resulted in different static and dynamic mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The shear forces might cause unselective scission of the rubber main chains and the reduction of the performance of RR particles. 39 The crosslink density of NR particles decreased from 7.2×10 À4 mol/cm 3 to 6.1×10 À4 mol/cm 3 (RR 1 ) and 5.5×10 À4 mol/cm 3 (RR 2 ) after rubber regeneration. The immobilized fraction of rubber chains decreased with decreasing crosslink density of RR because of the vulcanized network is partially broken-up which increased the chain mobility and flexibility of the polymer, while lower chain restriction leads to low rigidity and modulus after regeneration.…”
Section: Swelling Propertiesmentioning
confidence: 92%
“…The chemical structure of the r-SSs obtained by thermo-oxidative reclamation under different temperatures were characterized and compared with pure silica, as shown in Figure 2. All the r-SSs exhibits C-H stretching vibration of -CH2groups in the rubber backbone at 2916 and 2850 cm -1 , CH2-bending vibration at 1450 cm -1 , -CH3 bending vibration at 1374 cm -1 , and Si-O stretching of Si-alkoxy compound at 1070 and 950 cm -1 which is defined as TESPT characteristic peaks by Chorai et al 14 The broad peak at 3442 cm -1 corresponds to -OH stretching of Si-OH in silica.…”
Section: X-ray Diffraction (Xrd) Pattern Was Measured On a Bruker D8 ...mentioning
confidence: 99%